基於磁化率測定良渚甁窯北村遺址中紅燒土建築材料的經熱溫度 - 王慶宇; Wang Qingyu (중국학보, 2025)
소토재료는 가장 이른 인공 건축 재료로서 인류의 주거 환경을 근본적으로 개선하였다. 학계에서는 소토(burnt earth)건축의 형성 원인에 대해 인위적인 고온 처리, 화재 소실, 유기적 폐기 풍습, 전쟁으로 인한 방화 등의 다양한 견해가 존재한다. 선사 시대 건축에서 소토재료의 가열 온도에 대한 연구는 소위 ‘소토 건축’의 기원을 탐구하고 선사 건축사 연구를 풍부하게 하는 데 도움이 된다. 본 연구는 량주(良渚) 문화 병요(瓶窯) 베이춘(北村) 유적에서 출토된 소토 시료의 가열 온도를 자기감수 율 분석법으로 측정하였다. 그 결과, 두 점의 소토 시료는 모두 현장에서 채취한 점토로 나무 뼈대나 갈대를 감싸 벽체를 구성한 뒤, 인위적으로 가열하여 만들어진 건축 재료임이 드러났으며, 가열 온도는 약 600~700℃로 추정된다. 이는 해당 시료가 건축 부재였다는 가설을 뒷받침한다. 이는 량주 문화시기, 태호 유역의 선민들이 이미 불을 자유자재로 다루고 이를 주거 건축에 활용하였으며, 그 기술이 상당히 발달했음을 시사한다. Fired clay materials, as the earliest man-made building materials, fundamentally improved human living environments. In academic discussions on the origins of red-fired earth architecture, various hypotheses have been proposed, including intentional firing, accidental burning, ritual abandonment, and destruction by warfare. Studying the heating temperatures of fired materials in prehistoric architecture can help explore the origins of such constructions and enrich the study of prehistoric architectural history. This research analyzes the heating temperatures of fired clay samples from the Beicun site at the Liangzhu culture’s Pingyao region using the magnetic susceptibility method. Results show that two red-fired clay samples were likely made from locally sourced clay, wrapped around wooden frames or reed structures to form walls, and subsequently fired intentionally, reaching temperatures of 600-700°C. This supports the hypothesis that the samples served as architectural components. The findings indicate that during the Liangzhu cultural period, the ancestors living around the Taihu Lake Basin had already mastered fire control for architectural purposes and possessed relatively advanced construction techniques.